Effectiveness of Direct-acting Antivirals for the Treatment of Chronic Hepatitis C in Rwanda: A Retrospective Study. (6th June 2020) - Nsanzimana, Sabin; Penkunas, Michael J; Liu, Carol Y; Sebuhoro, Dieudonne; Ngwije, Alida; Remera, Eric; Umutesi, Justine; Ntirenganya, Cyprien; Mugeni, Soline D; Serumondo, Janvier
Abstract: Background: Direct-acting antivirals (DAAs) are becoming accessible in sub-Saharan Africa. This study examined the effectiveness of DAAs in patients treated through the Rwandan national health system and identified factors associated with treatment outcomes. Methods: This retrospective study used data from the national hepatitis C virus (HCV) program for patients who initiated DAAs between November 2015 and March 2017. Sustained virological response at 12 weeks after treatment (SVR12) was the primary outcome. Logistic regression models were fit to estimate the relationship between patients' clinical and demographic characteristics and treatment outcome. Results: 894 patients started treatment during the study period; 590 completed treatment and had SVR12 results. Among the 304 patients without SVR12 results, 48 were lost to follow-up and 256 had no SVR12 results but clinical data indicated they likely completed treatment; these patients were classified as nonvirological failure because viral clearance could not be determined. In a per-protocol analysis of 590 patients with SVR12 results, SVR12 was achieved in 540 (92%), and virological failure occurred in 50 (8%). Pretreatment HCV RNA above the median split was associated with virological failure. Intention-to-treat analyses including all patients showed that SVR12 was achieved in 540 (60%), with nonvirological failure in 304 (34%) and virological failure in 50 (6%). Patients in Western Province were more likely to experience nonvirological failure than patients in Kigali, likely owing to the 5–7-hour travel required to access testing and treatment. Conclusions: DAAs were effective when implemented through the Rwandan national health system. Decentralization and enhanced financing are underway in Rwanda, which could improve access to treatment and follow-up as the country prepares for HCV elimination. Abstract : Direct-acting antivirals are >90% effective in treating hepatitis C virus infection in Rwanda when treatment and follow-up schedules are kept. High pretreatment viral loads contribute to virological failure. Decentralizing services, reducing travel time, will help remove barriers to treatment completion.